Indigenous Wāhine Talking Critically in the Museum Space. Issue 1 (1st July 2022) - Cobley, Joanna; Wilson-Hokowhitu, Nālani; Mills, Maree; Yates, Rachel
Abstract : As greater numbers of community groups experience social disconnect, museums need to find better methods of engagement in order to remain relevant. We know that museums are no longer neutral spaces; in fact, they have a role to play in activism, which means they can shift their mission to support local communities celebrate and protect their Indigenous heritage (Drubay and Singhal 2020; Message 2018; Shelton 2013). What follows is a meditation by researchers in Aotearoa New Zealand who engage with Pacific-Indigenous concepts and museum practice in unique ways. Our big idea is to see "Oceania through Indigenous eyes" (Lagi-Maama 2019: 291) and, in particular, the eyes of Nālani Wilson-Hokowhitu with mo'okū'auhau to Kalapana, Hawai'i, and Moloka'i Nui a Hina; Maree Mills with whakapapa to Tongariro, Taupō, and Ngāti Tūwharetoa; and Rachel Yates, who hails from Vaisala, Sāmoa. As a collective, their curatorial talanoa kōrero / mo'olelo /stories connect to current debates in the museum world where local problems need local solutions. In this instance, Wilson-Hokowhitu and Mills share the ideas that shaped their mahi at Waikato Museum Te Whare Taonga o Waikato in Hamilton, and Yates has just finished a COVID-19 project as Curator of Pacific Cultures at the Museum of New Zealand Te Papa Tongarewa in Wellington.